2021
DOI: 10.1007/s11136-021-02813-5
|View full text |Cite
|
Sign up to set email alerts
|

Mental well-being of the general population: direct and indirect effects of socioeconomic, relational and health factors

Abstract: Purpose The aim of this study was to analyse the association between individual mental well-being and social, economic, lifestyle and health factors. Methods Cross-sectional study on a representative sample of 13,632 participants (> 15y/o) from the Catalan Health Interview Survey 2013–2016 editions. Mental well-being was assessed with the Warwick–Edinburg Mental Well-being Scale (WEMWBS). Linear regressions were fitted to associate well-being and sociod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 65 publications
2
14
0
1
Order By: Relevance
“… 36 , 61 Interestingly, previous studies have reported that, for people living in Spain, social support is one of the factors most closely associated with individual mental wellbeing 61 , 62 ; furthermore, there is a notable effect gradient from low to high mental wellbeing in accordance with financial difficulties. 61 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 36 , 61 Interestingly, previous studies have reported that, for people living in Spain, social support is one of the factors most closely associated with individual mental wellbeing 61 , 62 ; furthermore, there is a notable effect gradient from low to high mental wellbeing in accordance with financial difficulties. 61 …”
Section: Discussionmentioning
confidence: 99%
“…36,61 Interestingly, previous studies have reported that, for people living in Spain, social support is one of the factors most closely associated with individual mental wellbeing 61,62 ; furthermore, there is a notable effect gradient from low to high mental wellbeing in accordance with financial difficulties. 61 Psychological therapy, also called talking therapy, is a type of mental health treatment, alone or with medication. 63 Participants with lower job engagement and mental wellbeing were more likely to be in psychological therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature on health and social science is filled with the growing number of studies with regard to the effects of income, poverty, and social policies on a person's physical and mental well-being ( 4 , 5 ). Several studies are available in the literature which supports the notion that the socioeconomic well-being of the individuals Wanberge et al ( 6 ) and Soldevila-Domenech et al ( 7 ) or its related factors such as income Niessen et al ( 8 ), education Montez et al ( 9 ), and occupation Álvarez-Fernández ( 10 ) significantly affect the person's health condition. These studies are noted that social as well-economic factors are more important for health.…”
Section: Introductionmentioning
confidence: 77%
“…Test re-test reliability was also high at .83 (Stewart-Brown et al, 2011;Tennant et al, 2007). WEMWBS also demonstrated good discriminant, construct, and content validity (Dong et al, 2019;Soldevila-Domenech et al, 2021;Stewart-Brown et al, 2011;Taggart et al, 2013).…”
Section: Warwick-edinburg Mental Well-being Scale (Wemwbs)mentioning
confidence: 87%